Feasibility of Waste Calicut Tiles as Aggregates in Structural Concrete - Jayasekara, D.A.B.P.M.; Jayathilaka, S.T.N.; Somarathna, H.M.C.C. (University of Jaffna, 2022)
This study is intended to investigate the feasibility of using Calicut Tile Aggregates (CTA) sourced from industrial waste and construction and demolition waste as a replacement for Natural Aggregates (NA) use in the construction industry. An experimental program was conducted regarding the characteristics of Natural Coarse Aggregates (NCA), CTA, and the characteristics of concrete containing CTA. The results of the investigation conducted on aggregates revealed that there is a significant difference between the characteristics of NCA and CTA such as particle size distribution, bulk density, and specific gravity. Subsequently, concrete specimens were cast by replacing the NA from CTA in the proportions of 0%, 20%, 40%, 60%, 80%, and 100%, and density, and compressive strength were investigated to study the characteristics of concrete with CTA. According to the overall results of the study, a range of concrete with up to 40% replacement ratio was identified as the optimum range for replacement of CTA in the concrete mix with marginal deviations of characteristics compared to conventional concrete.
Keywords: Calicut tile aggregates; Coarse aggregates; Construction and demolition waste; Recycled aggregates; Recycled aggregates concrete